SOME REMARKS ON THE ARCHAEOLOGICAL SITE OF MUGTEPA (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes certain scholarly data regarding the study of the urban site of Mugtepa, its chronological dating, and its defensive system.